Characterization of edible soldier fly protein and hydrolysate altered by multiple-frequency ultrasound: Structural, physical, and functional attributes - Mintah, B.K.; He, R.; Dabbour, M.; Xiang, J.; Hui, J.; Agyekum, A.A.; Ma, H. (Process Biochemistry, 2020)
The effect of conventional (control), and different ultrasonic treatment modes (fixed, and sweep frequency ultrasound) on structural, physical and functional traits of soldier fly (Hermetia illucens) larvae protein preparations and hydrolysates were examined. Ultrasonication significantly increased lightness (L*) of protein isolates by x 7.46 % compared to control. Sonic-treated (particularly sweep-type) isolates and hydrolysates showed significant increases in thiol value, reconstitutability function (pH 2–10), and surface charge; and significant decreases in turbidity, and particle size, relative to controls. Protein isolates were characterized by higher molecular weight (MW) using SDS-PAGE, whereas hydrolysates were lower (with no observable variances). By numerical estimation, hydrolysates (especially the sweep-treated) showed significantly lower MW (< 1000 Da). Deconvoluted FTIR spectra (α-helix, β–sheet/turn, random coil fractions), and UV spectra analyses showed differences in samples. Treatment type (sweep/ fixed frequency ultrasound) could be used to alter protein structure, modify functionality, and thereby usage of H. illucens protein/hydrolysate preparations.
Research Article
Keywords: Molecular weight; Functionality; Edible insect protein; Ultrasonication; Enzymolysis